Mental strength and coping strategy of confined athletes dealing with COVID-19 - El Moutaraji, I.; Lotfi, S.; Talbi, M. (International Journal of Human Movement and Sports Sciences, 2021)
Due to this unexpected pandemic situation, the objective of this study is to explore the mental strength of elite athletes and their coping strategies to manage stress in different types of sports and according to their level of competition. 344 competitive athletes responded to a questionnaire on the training characteristics during this period, a Sports Mental Toughness Questionnaire to assess mental strength and coping strategies to manage stress wasassessed by the Athletic Coping Skills Inventory ACSI-28. The data were analyzed by ANOVAI. We found that the coping strategies adopted by elite athletes during this pandemic period vary significantly depending on the type of sport practiced, namely in terms of confidence and achievement motivation, freedom from worry and coping with adversity. We also found that coping strategies to manage stress have significant relationship with level of competition in terms of goal setting and mental preparation. For mental strength we found significant variation in self-confidence and control depending on the type of sport practiced. Also, depending on the level of competition, the control dimension varied significantly. It is suggested that the mental health for professional athletes be carefully managed during confinement to anticipate a possible recurrence of this epidemic.